Progress in Epitaxial Thin‐Film Na3Bi as a Topological Electronic Material. Issue 11 (3rd February 2021) - Di Bernardo, Iolanda; Hellerstedt, Jack; Liu, Chang; Akhgar, Golrokh; Wu, Weikang; Yang, Shengyuan A.; Culcer, Dimitrie; Mo, Sung‐Kwan; Adam, Shaffique; Edmonds, Mark T.; Fuhrer, Michael S.
Abstract: Trisodium bismuthide (Na3 Bi) is the first experimentally verified topological Dirac semimetal, and is a 3D analogue of graphene hosting relativistic Dirac fermions. Its unconventional momentum–energy relationship is interesting from a fundamental perspective, yielding exciting physical properties such as chiral charge carriers, the chiral anomaly, and weak anti‐localization. It also shows promise for realizing topological electronic devices such as topological transistors. Herein, an overview of the substantial progress achieved in the last few years on Na3 Bi is presented, with a focus on technologically relevant large‐area thin films synthesized via molecular beam epitaxy. Key theoretical aspects underpinning the unique electronic properties of Na3 Bi are introduced. Next, the growth process on different substrates is reviewed. Spectroscopic and microscopic features are illustrated, and an analysis of semiclassical and quantum transport phenomena in different doping regimes is provided. The emergent properties arising from confinement in two dimensions, including thickness‐dependent and electric‐field‐driven topological phase transitions, are addressed, with an outlook toward current challenges and expected future progress. Abstract : Na3 Bi displays remarkable thickness‐dependent properties, from bulk topological Dirac semimetal to wide‐bandgap 2D topological insulator in ultrathin films with electric‐field‐driven topological switching. An overview of the recent progress on Na3 Bi is presented, with a focus on technologically relevant large‐area epitaxial films, and an outlook toward challenges and opportunities for applications to the next generation of topological electronic and spintronic devices.